2022
DOI: 10.1920/re.ifs.2022.0234
|View full text |Cite
|
Sign up to set email alerts
|

Annual report on education spending in England: 2022

Abstract: This report is the third in a series of annual reports on education spending in England. The authors gratefully acknowledge the support of the Nuffield Foundation, which has funded this series of annual reports (grant number EDO/43355). The Nuffield Foundation is an independent charitable trust with a mission to advance educational opportunity and social well-being. It funds research that informs social policy, primarily in Education, Welfare and Justice. It also provides opportunities for young people to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…This mostly reflects increases in funding announced at recent spending reviews. The figures for England are also higher than we have previously published as we include the grant for additional employer pension contributions (Drayton et al, 2022). This ensures consistency with figures for other nations.…”
Section: Comparing Spending Per Pupil Across Uk Nationssupporting
confidence: 72%
“…This mostly reflects increases in funding announced at recent spending reviews. The figures for England are also higher than we have previously published as we include the grant for additional employer pension contributions (Drayton et al, 2022). This ensures consistency with figures for other nations.…”
Section: Comparing Spending Per Pupil Across Uk Nationssupporting
confidence: 72%
“…A large part of the reason for these low pay increases is the squeeze on college budgets over the last decade. In our recent annual report on education spending (Drayton et al, 2022), we showed that between 2010-11 and 2019-20, public spending per student (aged 16-18) fell by 14% in colleges, while spending on classroom-based adult education almost halved in the same period. These cuts to post-16 education funding have made it difficult for colleges to allocate money towards higher levels of staff remuneration.…”
Section: The Long Decline In Recommended Pay Levelsmentioning
confidence: 85%
“…College leaders face the challenge of finding money within already stretched budgets to fund pay increases for their staff. Between 2009-10 and 2019-20, public spending per student aged 16-18 declined by 12% in colleges in real terms, while spending on classroom-based adult education almost halved (Drayton et al, 2022). These cuts to the post-16 education budget have made it difficult for college leaders to allocate more money to higher pay levels.…”
Section: Median Salary 2022-23 Pricesmentioning
confidence: 99%